Hydrogen absorption characteristics of MmNi5 as hydrogen storage medium - Nor Aishah Saidina Amin; Hamdani Saidi, 1953-; Rosli Mohd. Yunus; Anwar Johari, 1970-; International Conference on Advances In Strategic Technologies (ICAST 2000) (2nd :2000 : Selangor) (Skudai : Universiti Teknologi Malaysia, 2000)
42